2012
DOI: 10.1590/s1020-49892012000500010
|View full text |Cite
|
Sign up to set email alerts
|

Current depression among women in California according to residence in the California-Mexico border region

Abstract: Similar prevalences of current depression were observed among those who live in the border region of California and in those who do not, but the relationship between depression and health status, health care access, and binge drinking varied by border region residence. Ideally, future surveillance of depression and its predictors along the Mexico-California border will be conducted binationally to inform interventions and tracking such as the Healthy Border Program's objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…Ryan-Ibarra and colleagues similarly found that the prevalence of depression did not vary in relation to border residence status among California women [57]. In this study, binge drinking predicted depression in both border and non-border areas of California [57]. In our study, binge drinking was not associated with women’s depression; however, the presence of alcohol-related problems was.…”
Section: Discussionsupporting
confidence: 54%
“…Ryan-Ibarra and colleagues similarly found that the prevalence of depression did not vary in relation to border residence status among California women [57]. In this study, binge drinking predicted depression in both border and non-border areas of California [57]. In our study, binge drinking was not associated with women’s depression; however, the presence of alcohol-related problems was.…”
Section: Discussionsupporting
confidence: 54%
“…Although many studies reported a high prevalence of depression among immigrants compared to non-immigrants [18,19,30], our findings align with other studies that found a lower prevalence [65], consistent with the healthy migration hypothesis. Our results further confirmed this hypothesis among recent immigrants, consistent with past studies from the United States [66] and Canada [65]. Conversely, other studies have reported high risk among recent migrants [18,29] and risk regardless of time since migration [65].…”
Section: Depressionsupporting
confidence: 93%